2015
DOI: 10.1177/1535370215609692
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapies in the treatment of diabetic retinopathy and keratopathy

Abstract: Nonproliferative diabetic retinopathy (DR) is characterized by multiple degenerative changes that could be potentially corrected by stem cell therapies. Most studies so far have attempted to alleviate typical abnormalities of early retinopathy, including vascular hyperpermeability, capillary closure and pericyte dropout. Success was reported with adult stem cells (vascular progenitors or adipose stem cells), as well as induced pluripotent stem cells from cord blood. The cells were able to associate with damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 136 publications
(173 reference statements)
0
20
0
Order By: Relevance
“…Still others have shown that transient in vitro inhibition of TGF-beta improves the function of circulating endothelial progenitor cells from diabetic subjects and enhances the engraftment of these cells in eyes with diabetic retinopathy (Bhatwadeker et al, 2010). Such a treatment may potentially enhance the therapeutic potential of the CD34 + cells from both bone marrow and peripheral blood and normalize dysfunctions induced by the diabetic environment (Kramerov and Ljubimov, 2016). …”
Section: Methods To Enhance Therapeutic Effects Of Bone Marrow Stementioning
confidence: 99%
“…Still others have shown that transient in vitro inhibition of TGF-beta improves the function of circulating endothelial progenitor cells from diabetic subjects and enhances the engraftment of these cells in eyes with diabetic retinopathy (Bhatwadeker et al, 2010). Such a treatment may potentially enhance the therapeutic potential of the CD34 + cells from both bone marrow and peripheral blood and normalize dysfunctions induced by the diabetic environment (Kramerov and Ljubimov, 2016). …”
Section: Methods To Enhance Therapeutic Effects Of Bone Marrow Stementioning
confidence: 99%
“…Specific gene therapy of limbal compartment harboring LESC was able to restore the marker expression levels and accelerate healing of large epithelial wounds (Saghizadeh et al, 2014). In severe cases of diabetes and with pronounced neuropathy, LESC may become seriously dysfunctional (Ueno et al, 2012; Zhou et al, 2015), and a transplantation of healthy cells may become an option (Kramerov and Ljubimov, 2016). Normal LESC may be obtained from donors, especially in cases of bilateral stem cell deficiency.…”
Section: Treatment Possibilitiesmentioning
confidence: 99%
“…Nowadays, a growing number of diseases can be improved via wide applications of stem cell transplantation, such as congenital cataract [12], diabetic retinopathy and keratopathy [13], myocardial infarction [14], ocular surface burns [15, 16], serious skin burns [17, 18], Parkinson's disease [19], Huntington's disease [20], and especially DFU [21]. Accumulating evidence has pointed out that mesenchymal stem cells (MSCs) may enhance wound healing [2224] and be served as a cell source for many tissue engineering applications including bone regeneration [25], cartilage regeneration [2628], myocardial regeneration [29], neurogenesis [30, 31], inflammatory bowel diseases [32], and DFU [33, 34].…”
Section: Introductionmentioning
confidence: 99%